THE SILENCE OF THE EXCLUDED. A PERSPECTIVE OF LINGUISTIC PRECONCEPTION IN BRAZIL - Barreto de Souza e Sá, Daniel (LINKSCIENCEPLACE, 2026)
Social exclusion occurs on several levels. It is interesting to this work, however, to analyze and discuss exclusion by language; Its causes and consequences. In this hypothetical view, linguistic prejudice is a paradoxical form of censorship, because the excluded can speak, but there is, outside of their social life, who wanted to hear it. In Brazil, social exclusion is a reflection of the inequality generated by the poor distribution of income. The gap between the rich and the poor separates the country in two: on the one hand the "Senzala" (poor - descendants of the slaves), on the other the "Great House" (rich - descendants of the settlers). This separation, as in the metaphor of Gilberto Freyre, is also seen in the field of language, since there is a language spoken and understood by the "Casa Grande" and another completely different from the "Senzala". Such a distinction is even visible in grammar, since the "right language," the standard, was instituted from the mode of speech of the nobles. Such speakers, considered literate, have a privileged linguistic variant, not only for access to education, but also for remaining in the ruling classes. It means that language is an instrument of power, capable of promoting the maintenance or rupture of social ties, the preservation or extinction of individualities, inclusion or social exclusion. Therefore, in a reflection of the history of Brazil, the speaker who does not express himself adequately or who does not dominate the "standard dialect" is dominated, subjugated and stigmatized. Sociolinguistics takes care of these factors and the pressure that they exert on the language, however the objective here is not only to reproduce them, but correlates them to article 5, section VII, of the Brazilian Magna Carta, regarding freedom of expression, In order to expose the problems of this analogy.